Effect of High-Pressure Processing on Color, Texture and Volatile Profile During Sardine Refrigeration - Lama Ismaiel; Ancuta Nartea; Benedetta Fanesi; Paolo Lucci; Deborah Pacetti; Henry Jaeger; Felix Schottroff (Foods)
Extending sardine shelf life while maintaining their quality is challenging even with non-thermal technologies like high-pressure processing (HPP). This study examines the effects of HPP at 400 and 600 MPa for holding times of 1, 2.5, 5, and 10 min on fresh sardines during 14 days of cold storage. Physicochemical attributes, including texture, color, and volatile organic profiles, were assessed. Increasing both pressure and holding times resulted in increased levels of hardness, chewiness, and L* during storage. HPP-treated samples maintained lower a* values compared to the control ones by the end of the experiment. The volatile profile of HPP samples was significantly affected compared to control samples, which developed exclusively volatile oxidation compounds (hexanal and 2,4-hexadienal) by the end of the storage. Volatile groups such as aldehyde and ketone were slightly impacted by both storage and HPP treatments (i.e., pressure and holding time). Ketone levels were consistently lower in all treated samples, ranging from 25.3% to 33.6% at 400 MPa and 600 MPa, respectively, compared to the control samples, which had a ketone level of 40.5% on day 14. These findings indicate the potential of HPP in prolonging shelf life and preserving quality in the sardine market.